2012
DOI: 10.1186/1297-9716-43-56
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Salmonella typhimurium delivering DNA vaccine encoding duck enteritis virus UL24 induced systemic and mucosal immune responses and conferred good protection against challenge

Abstract: Orally delivered DNA vaccines against duck enteritis virus (DEV) were developed using live attenuated Salmonella typhimurium (SL7207) as a carrier and Escherichia coli heat labile enterotoxin B subunit (LTB) as a mucosal adjuvant. DNA vaccine plasmids pVAX-UL24 and pVAX-LTB-UL24 were constructed and transformed into attenuated Salmonella typhimurium SL7207 resulting SL7207 (pVAX-UL24) and SL7207 (pVAX-LTB-UL24) respectively. After ducklings were orally inoculated with SL7207 (pVAX-UL24) or SL7207 (pVAX-LTB-UL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 45 publications
(46 reference statements)
5
34
0
Order By: Relevance
“…In addition, the levels of serum IgG were significantly higher than those of serum IgA. This suggested that IgG is the main antibody against DPV, which coincided with previous studies (8,21).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, the levels of serum IgG were significantly higher than those of serum IgA. This suggested that IgG is the main antibody against DPV, which coincided with previous studies (8,21).…”
Section: Discussionsupporting
confidence: 89%
“…Serum IgG and IgA play critical roles in humoral immunity against specific antigens (21,33). In this study, the DPV attenuated vaccine enhanced production of both IgA and IgG antibodies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations